Evaluasi Pengelolaan Aset Publik untuk Mencapai Pembangunan Berkelanjutan di Kota Serang Provinsi Banten - Hasyim Adnan (PANDITA: Interdisciplinary Journal of Public Affairs, 2025)
This study aims to evaluate the management of public assets in Serang City and its contribution to the achievement of sustainable development. Public assets, such as land, buildings, and infrastructure, serve as strategic resources in supporting economic, social, and environmental programs. Effective and optimal asset management not only enhances public service efficiency but also contributes to long-term community welfare and environmental sustainability. The findings reveal that Serang City faces several challenges in managing public assets, including the absence of an integrated data system, inadequate maintenance mechanisms, and limited utilization of assets for productive activities. Furthermore, institutional coordination and budget allocation for asset management remain suboptimal. Despite these challenges, the study identifies potential opportunities for improvement, such as the digitalization of asset management systems, reinforcement of regulatory frameworks, and capacity-building for human resources. Involving local communities in asset monitoring and utilization is also highlighted as a strategic recommendation to ensure transparency and accountability. With better governance, Serang City has the potential to accelerate the achievement of sustainable development goals, particularly in promoting inclusive economic growth, enhancing social welfare, and preserving the environment. The study concludes that strengthening asset management is a critical step toward ensuring that public resources are managed effectively for the benefit of present and future generations.